The big picture of sexual science - Howard Chiang; James Poskett (BJHS Themes)
This article identifies a few paradigmatic ways whereby the big picture of sexual science has been made possible, especially through a diversification in the uneven but interconnected geography of scientific practice. It focuses on the ways in which the life and work of individual researchers, institutional settings and journal circulations have anchored the development of narratives about the history of sexual science. By delineating the shifting cultural geography, epistemological premise and conceptual innovations in sexological research, it is possible to cast the co-constituted nature of knowledge making as an enterprise simultaneously local and global in its reach. The rise of modern sexual science represented as much a gestalt counterpart to the evolutionary paradigm as a response to the shifting terrains of religious and legal governance in the regulation of sexuality.